Kader Pusat Informasi Dan Konseling Remaja (PIK-R) Dalam Siklus Reproduksi Di Kelurahan Kenali Asam Bawah Kecamatan Kota Baru Jambi - Dwi Noerjoedianto; Fitria Eka Putri; Arnild Augina Mekarisce (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2019)
ABSTRACT KB Purwosari village is one of the KB villages in the Kenali Asam Bawah Kelurahan, Kota Baru Jambi District. During 2017 since it was set, only the stages of socialization to the community about the importance of the existence of the KB village, and the formation of poktan (activity groups). Divided into 5 groups, namely the Youth Family Development Group (BKR), Prosperous Family Income Improvement Efforts (UPPKS), Toddler Family Development (BKB), Elderly Family Development (BKL) and Managers of the Youth Information and Counseling Center (PIK-R). Community service is carried out by stages in formulating schedules and activity plans, providing material to members of the PIK-R poktan and BKR poktan, KIE media simulation to PIK-R poktan and BKR poktan members, home visits (visite), mass media exposure, home data display and monitoring and evaluating success. Has shown success as evidenced by the increase in pre-test results and post-test results, in the 7 categories of variables measured, while those that need to be followed up on 3 variables that have not significantly changed, (the achievement value remains no change), namely in the Triad category KRR on healthy family planning, use of contraceptives, and routine check-ups during pregnancy. Activities initiated by groups of activities both PIK R RT 03 and BKR RT 18 really gave a positive warrants and aura to the KB Village. The continuity of activities with the support of the puskesmas and kelurahan is very good.